Male urethral sarcoma: a case report and literature review - Magno Almeida Nogueira (Einstein (São Paulo))
Urethral tumors are rare and aggressive. They usually affect men (2:1) and occur more commonly in white (85% of cases). Soft tissue sarcomas are a heterogeneous group of tumors that arise from embryonic mesoderm. It represents 1% of all cases of urinary tract malignancies and rarely primary affect the ureter. We report a case of male urethral sarcoma. To date, only two similar cases have been published in literature.